AKTIVITAS FISIK, DURASI PENYAKIT DAN KADAR GULA DARAH PADA PENDERITA DIABETES MELLITUS (DM) TIPE 2 - Yessi Alza; Yuliana Arsil; Yessi Marlina; Lidya Novita; Niken Dwi Agustin (Jurnal GIZIDO, 2020)
Diabetes mellitus (DM) is a chronic disease caused by the inability of the pancreas to produce enough insulin, or the body cannot effectively use the insulin produced by the pancreas. Regular aerobic physical activity in people with a diagnosis of DM can improve insulin sensitivity. The prevalence of DM in Indonesia based on Basic Health Research (Riskesdas) in 2018 is 10.9% while in Riau province occupies the third-highest rank in Indonesia. This study aims to determine the description of physical activity and blood sugar levels in people with type 2 diabetes mellitus at the Sidomulyo Health Center, Pekanbaru City. This study is descriptive with cross-sectional design. The sampling technique in this study was a total sampling of 24 people with DM type 2. Data collection for physical activity variables was carried out using a questionnaire included in PAL (Physical Activity Level). Measurement of blood sugar levels in patients with DM is done by taking respondent capillary blood then measured using a glucometer (Easy Touch GCU). Univariate analysis was carried out to analyze the variables of physical activity and blood sugar levels which were then presented in the form of frequency distribution tables and narratives. The results showed a description of the level of physical activity in respondents who suffer from DM as many as 16 people (66.7%) with mild physical activity levels, and 8 people (33.3%) with moderate levels of physical activity. Description of fasting blood sugar levels of respondents as many as 19 people (79.2%) had controlled fasting blood sugar levels, and 5 people (20.8%) had uncontrolled fasting blood sugar levels.